1402 Family integrated care: understanding the views and experiences of staff on a tertiary neonatal unit. (17th August 2022) - Clements, Rebecca; Bean, Anne; Hoyle, Emily
Abstract : Aims: Family integrated care (FiCare) supports and educates families to become integral participants in their baby's care in partnership with the neonatal team. It is widely endorsed as the optimum model of neonatal care and BAPM suggest all neonatal units should implement this. 1 It has many benefits to baby, parents and staff including; reduced length of stay, increased weight gain, increased breastfeeding rates at discharge, and reduced readmission rates to hospital. 2, 3 In order to implement this as routine practice within our tertiary level neonatal unit, we identified the importance of engaging staff and therefore sought their opinions and experiences of this model of care. Our aim was to identify themes and trends from which we could develop and embed a sustainable model of FiCare on our neonatal unit. Methods: An online staff survey was created, and the link distributed to all staff working on the neonatal unit to complete. This survey consisted of 15 questions relating to different aspects of FiCare and provided areas for comments. It was posted for 4 weeks, and following this, results were analysed using the Microsoft forms analysis tool to identify themes and areas of excellent practice and areas for development. Results: 82 staff members on the neonatal unit completed this survey ( figure 1 ), and most viewed the implementation of this model as a positive process with many benefits identified ( table 1 ). Feedback included 'parents should be involved in all aspects of their baby's care', 'it is their child', 'model will help with bonding'. Medical staff highlighted parents could be more involved in decision making but raised concerns that having parents present for invasive procedures could be distressing for them, and this could distract the practitioner causing them to lose focus. However, practitioners described the value of parent engagement in ward rounds, and in cares for their infant. Nursing staff discussed how they planned routines with the parents to ensure participation at every opportunity, and the importance of regular communication. There was however concern from some that there is still an inconsistent approach to FiCare on the unit preventing parental empowerment, and was described as practitioner dependent. Some also questioned whether non-English speaking families were less involved in their babies care due to the language barrier. A recognised challenge for the integration of FiCare on the neonatal unit will be the involvement of siblings as COVID-19 restrictions ease. Conclusion: This survey has highlighted the importance of staff involvement in developing this model of care within the NICU setting. In order to further develop this model of care we will undertake a survey of parent's views and experiences. In addition it is essential that we establish regular cot-side use of interpreting services to overcome the barriers faced by non-English speaking families. References: FiCare: A framework for Practice. BAPM . 2021. Lee. Neonatal Nurs . 2018;26;24 :1-3. Karan. J Trop Pediatr . 1983;29 (2):115-8.